Adoptive Transfer of Human Gingiva‐Derived Mesenchymal Stem Cells Ameliorates Collagen‐Induced Arthritis via Suppression of Th1 and Th17 Cells and Enhancement of Regulatory T Cell Differentiation. Issue 5 (23rd April 2013) - Chen, Maogen; Su, Wenru; Lin, Xiaohong; Guo, Zhiyong; Wang, Julie; Zhang, Qunzhou; Brand, David; Ryffel, Bernhard; Huang, Jiefu; Liu, Zhongmin; He, Xiaoshun; Le, Anh D.; et al.
Abstract: Objective: Current approaches offer no cures for rheumatoid arthritis (RA). Accumulating evidence has revealed that manipulation of bone marrow–derived mesenchymal stem cells (BM‐MSCs) may have the potential to control or even prevent RA, but BM‐MSC–based therapy faces many challenges, such as limited cell availability and reduced clinical feasibility. This study in mice with established collagen‐induced arthritis (CIA) was undertaken to determine whether substitution of human gingiva‐derived mesenchymal stem cells (G‐MSCs) would significantly improve the therapeutic effects. Methods: CIA was induced in DBA/1J mice by immunization with type II collagen and Freund's complete adjuvant. G‐MSCs were injected intravenously into the mice on day 14 after immunization. In some experiments, intraperitoneal injection of PC61 (anti‐CD25 antibody) was used to deplete Treg cells in arthritic mice. Results: Infusion of G‐MSCs in DBA/1J mice with CIA significantly reduced the severity of arthritis, decreased the histopathology scores, and down‐regulated the production of inflammatory cytokines (interferon‐γ and interleukin‐17A). Infusion of G‐MSCs also resulted in increased levels of CD4+CD39+FoxP3+ cells in arthritic mice. These increases were noted early after infusion in the spleens and lymph nodes, and later after infusion in the synovial fluid. The FoxP3+ Treg cells that were increased in frequency mainly consisted of Helios‐negative cells. When Treg cells were depleted, infusion of G‐MSCs partially interfered with the progression of CIA. Pretreatment of G‐MSCs with a CD39 or CD73 inhibitor significantly reversed the protective effect of G‐MSCs on CIA. Conclusion: The role of G‐MSCs in controlling the development and severity of CIA mostly depends on CD39/CD73 signals and partially depends on the induction of CD4+CD39+FoxP3+ Treg cells. G‐MSCs provide a promising approach for the treatment of autoimmune diseases.